Revisiting the link between mission statements and organizational performance in the non-profit sector: The mediating effect of organizational commitment. Issue 1 (February 2016) - Macedo, Isabel Maria; Pinho, José Carlos; Silva, Anabela Martins
Abstract: Although mission statements are widely adopted as an important strategic tool, their effective influence on organizational performance are not firmly established due to a lack of consistent results in relevant literature. To shed light on this relationship, the present study proposes a model to examine the mediating role of organizational commitment in explaining and clarifying the mission-performance link. Another merit of this paper is to consider mission as a formative construct. Adopting a quantitative methodological approach, this study reports findings obtained from a representative sample of 112 non-profit health care organizations operating in Portugal. Our findings clearly demonstrate that the relationship between mission statements and organizational performance is better understood if the influence of organizational commitment, as a mediating variable of the aforementioned relationship, is taken into account. This study concludes by discussing conceptual contributions, limitations and possible future research avenues.